# Calculo Limites

Páginas: 2 (434 palabras) Publicado: 11 de noviembre de 2012
1-° Lim x2+3+4x+5x1 | (1)2+3+41+5 = 1+3+46 = 4+46 = 66 = 1T1 Y T7 |
2-° lim 3x+12x-5 x1/2 | 312+1212-5 = 32+122-5 = 3+221-5 = 52 -41 = -5/8T7|
3-° lim x2-93x+1 x3 | 32-933+1 = 9-99+1 = 010 = 0T7 |
4-° lim 2+y2+3y-1 y1 | 2+12+31-1 = 2+1+30 = 2+40 = 2+20 = 4/0 = ∞T1 Y T7 |
5-°Limite (7-2x) X2 | Lim 7 – 2x = lim 7 – 2(2) = lim 7 -4 = lim 3x2 x2T1 Y T5 |
6-° Limite (4x2-2x-6)x3 | Lim 4x2-2x-6 lim4(3)2-23-6x3 x3 lim 36-6-6 lim 24 T1 Y T5 |
7-° Limite (6-2x)x -4 | Lim 6-2x lim 6 –2(-4) lim 6+8lim 14 X -4 x -4 T1 Y T5 |
8-° Limite 8+t^3 x -2 | Lim 8+t3 lim 8+-23 lim 8-8 lim 0x-2 x -2 lim 0 T1 YT5 |
9-° Limite 7z2+14z-7z2 | Lim 7z2+14z-7 lim 72+142-7z2 z2 lim 14+28-7 lim 35 lim 5.91 T1 Y T5 |
10-° Limite(x2-8)(4x-8)x4 | Lim (x2-8)(4x-8) lim [4)2-8[44-8]x4 x4 lim (16-8)(16-8) lim (8)(8) lim 64 T1 Y T6 |
11-° Limite(6-3x)(3/5x -1) x -3 | Lim (6-3x)(35x-1 lim [6-3(-3)][35-3-1]x -3 x -3lim (6+9)(3/5(-333)) lim (15)(-1/5) lim -15 /5 lim -3 T1Y T6 |
12-° Limite (x2+1/9)(x-1/3)x -1/3 | Lim (x2+1/9)(x – 1/3) lim [(-1/3)^2 + 1/9)(-1/3 – 1/3)x -1/3 x - 1/3lim (1/9 + 1/9)( -1/3 – 1/3)lim (2/9)(-2/3)lim -4/27 T1 Y T6 |
13-° Limite (2/r + ½)(r^2 – 4/r)r 4 | Lim (2/r + ½)(r^2 – 4/r) lim (2/4 + ½)(4^2 – 4/4)r4...

Regístrate para leer el documento completo.